Transformative Pedagogy at the University of Sulaimani: Bridging Theory and Practice in Teacher Education - Amin, Choman Amin; Aziz, Khanda Aziz; Ali, Zana Ali; Saeed, Stam Saeed (Sulaimani Journal for Humanities, 2025)
This study evaluated the pedagogical programme at the University of Sulaimani by examining its effectiveness, strengths, and areas for improvement from the perspective of enrolled students. The research focused on several key areas, including teaching methods, curriculum relevance, assessment practices, technology integration, learning environment, and practical experience. A descriptive cross-sectional survey was used, with supplementary thematic analysis of open-ended responses, and census sampling targeted all 101 students enrolled in the programme. Data were gathered through a structured survey distributed via Google Forms, combining closed-ended and open-ended questions to capture both quantitative trends and qualitative insights. Quantitative data were analysed using descriptive statistics (frequencies, means) in SPSS version 26, while qualitative data underwent thematic analysis. Validity was supported through pilot testing, reliability checks, and triangulated review of qualitative responses. Findings revealed strong student satisfaction with the learning environment, teaching quality, and technology use. However, concerns were raised about limited practical experience, curriculum alignment with career goals, and inconsistent assessment methods. The study concludes that while the programme has a solid foundation, it requires improvements. Recommendations include increasing hands-on practice, reducing class size, updating materials, extending course duration, and using Kurdish to enhance accessibility
Keywords: Pedagogical Programme; University of Sulaimani; Teacher Education; StudentFeedback; Curriculum Evaluation; Practical Experience